CULTURAL AND ENTERTAINMENT INSTITUTIONS IN THE CITIES OF NORTHERN AZERBAIJAN (THE SECOND HALF XIX - EARLY XX CENTURY) - E. Vagabova (Гуманитарные и юридические исследования)
The article traces the main stages of the construction of cultural and entertainment institutions in the cities of Northern Azerbaijan.The article notes that it is with the revival of socio-political and cultural life, the development of architecture that construction of spectacular buildings is observed in Azerbaijani cities., With the reference to archival sources and additional literature, the author covers the construction of buildings for entertainment activities, initiated by theatrical figures, as well as local philanthropists and entrepreneurs both local and foreign. The proposed article also reveals the participation of urban self-government in such a signiicant event in the life of the cities of Northern Azerbaijan. It is concluded that, despite a number of bureaucratic issues, the construction of entertainment institutions continued, enriching the architectural image of cities. The article covers the theatrical, musical, ballet tours of famous and leading theater troupes, the 30th anniversary of the construction of the G. Z. Tagiyev Theater, which performed the hymn "General Tagiyev" written by Azerbaijani composer Uzeyir Hajibeyov. The author also highlights new productions of performances based on works by Azerbaijani, Russian and foreign authors. They played a signiicant and noble role in the cultural life of the Azerbaijani people, contributed to the implementation of a cultural upsurge, the development of aesthetic taste among the population, laid the foundations for the diversity of their cultural leisure.